2007
DOI: 10.1001/archderm.143.2.155
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Stimulation of De Novo Collagen Production Caused by Cross-linked Hyaluronic Acid Dermal Filler Injections in Photodamaged Human Skin

Abstract: To determine whether endogenous synthesis of new extracellular matrix may contribute to the degree and duration of clinical benefits derived from crosslinked hyaluronic acid dermal filler injections. Design:In vivo biochemical analyses after filler injections.Setting: Academic referral center.Participants: Eleven healthy volunteers (mean age, 74 years) with photodamaged forearm skin.Interventions: Filler and vehicle (isotonic sodium chloride) injected into forearm skin and skin biopsy specimens taken 4 and 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
336
2
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 405 publications
(363 citation statements)
references
References 41 publications
14
336
2
11
Order By: Relevance
“…Evidence suggests that MMP-1-mediated cumulative collagen damage is a major contributor to the phenotype of aged human skin. [32][33][34][35][36] However, molecular mechanisms underlying elevated expression of MMP-1 are not well understood.…”
mentioning
confidence: 99%
“…Evidence suggests that MMP-1-mediated cumulative collagen damage is a major contributor to the phenotype of aged human skin. [32][33][34][35][36] However, molecular mechanisms underlying elevated expression of MMP-1 are not well understood.…”
mentioning
confidence: 99%
“…It would be very arduous to recruit volunteers for a randomized placebo-controlled trial. Wang et al saline injections, was related with type I collagen deposition around the injection site [19] . Although both studies are not strictly equivalent, there is no reason to believe that LPOA skin would respond contrarily to forearm skin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Yoneda et al [20], in an animal model, highlighted that exogenous stabilized HA acts as a modulator of dermal fibroblast proliferation that modifies indirectly the synthesis of collagen. Finally, Wang et al [21] demonstrated that nonanimal stabilized HA injected into the dermal matrix is able to enhance the stimulation of de novo synthesis of type I collagen, possibly mediated by mechanical stretching and consequent activation of collagen-producing fibroblasts in the dermis.…”
Section: Discussionmentioning
confidence: 99%